2007
DOI: 10.1007/s00402-007-0509-2
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic reconstruction of chronic anteroinferior glenoid defect using an autologous tricortical iliac crest bone grafting technique

Abstract: Only a few reports exist on the management of severe anteroinferior glenoid defects in case of recurrent shoulder instability most of them including open approaches. We describe an all-arthroscopic reconstruction technique of the anteroinferior glenoid that includes an autologous iliac crest bone grafting using bio-compression screws and a capsulolabral repair using suture anchors. This technique recreates the bony and soft-tissue anatomy of the anteroinferior glenoid while preserving the integrity of insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 17 publications
0
73
0
5
Order By: Relevance
“…Although there are several studies on the treatment for glenoid bone loss [23,25,[33][34][35][36][37][38], bone defects of the humeral head have not been thoroughly evaluated. There is little consensus regarding surgical indications or standard treatments to reconstruct defects of the humeral head [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies on the treatment for glenoid bone loss [23,25,[33][34][35][36][37][38], bone defects of the humeral head have not been thoroughly evaluated. There is little consensus regarding surgical indications or standard treatments to reconstruct defects of the humeral head [22].…”
Section: Discussionmentioning
confidence: 99%
“…6 Other authors have described and reported bone block procedures for anteroinferior glenohumeral instability, but our technique is the first performed entirely arthroscopically without the use of screws. [7][8][9][10][11] The well-established advantages of using arthroscopy for shoulder stabilization include smaller incisions with less soft-tissue dissection and improved ability to completely inspect the glenohumeral joint and access all areas of the joint for repair, as well as preservation of external rotation. In case of mechanical inconsistency or absence of the soft tissues, it is possible to switch to an arthroscopically assisted Latarjet procedure that we have recently described.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,10 There are only a few published all-arthroscopic iliac crest graft augmentation techniques, including those of Taverna et al 11 using metal screws and, more recently, EndoButton devices (Smith & Nephew); Scheibel et al 12 with the use of bioabsorbable screws; and Anderl et al 13 with implant-free, Jebone graft reconstruction. 14 We consider our proposed technique to have several advantages (Table 2).…”
Section: Discussionmentioning
confidence: 99%